Novel heat-resistant Al-Si-Fe-Ni alloy for laser additive manufacturing and preparation method thereof

By introducing Fe and Ni elements into laser additive manufacturing, optimizing process parameters and forming eutectic AlFeNi cellular tissue, the problems of poor performance and difficult complex shape formation in high temperature environments are solved, and high efficiency is achieved. The formation of the new low-cost Al-Si-Fe-Ni alloy meets the needs of lightweight, high heat resistance and high strength in the fields of aerospace and other fields.

CN119265456APending Publication Date: 2025-01-07CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411631495.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing heat-resistant aluminum alloys have poor performance in high temperature environments, and traditional casting methods are difficult to form complex shapes. In laser powder bed melting technology, aluminum alloys are prone to thermal cracks, which cannot meet the lightweight and high heat resistance in aerospace and other fields. High strength requirements.

Method used

Laser additives are used to manufacture new Al-Si-Fe-Ni alloys. By introducing Fe and Ni elements, the raw material ratio and process parameters are optimized. Laser powder bed melting technology is used to form layer by layer under protective atmosphere to form eutectic AlFeNi cell-like tissues. , improve high temperature mechanical properties.

Benefits of technology

It achieves excellent mechanical properties at room temperature and high temperature, with a density of 99.6%, high tensile strength at room temperature and excellent high temperature performance. It is suitable for the production of complex components, reducing manufacturing costs and processing difficulties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265456A_ABST
    Figure CN119265456A_ABST
Patent Text Reader

Abstract

The invention discloses a novel heat-resistant Al-Si-Fe-Ni alloy for laser additive manufacturing and a preparation method of the novel heat-resistant Al-Si-Fe-Ni alloy. The Al-Si-Fe-Ni heat-resistant alloy comprises 10-14 wt% of Si, 1.5-2.5 wt% of Fe, 1.5-2.5 wt% of Ni and the balance Al and inevitable impurities, forming is conducted through a laser powder bed melting method, and compact crack-free forming of the Al-Si-Fe-Ni heat-resistant alloy is achieved by optimizing printing process parameters. A proper amount of Fe and Ni elements are introduced into the Al-Si alloy with good formability, a eutectic AlFeNi cellular structure is formed at a high temperature, the high-temperature mechanical property of the alloy material is greatly improved, and meanwhile, the room-temperature performance and the high-temperature performance are jointly improved by further optimizing process parameters and alloy components. The alloy material provided by the invention is good in formability, high in density, good in room-temperature performance, excellent in high-temperature performance and convenient to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new material preparation, and in particular to a laser additive manufacturing novel heat-resistant Al-Si-Fe-Ni alloy and a preparation method thereof. Background Art

[0002] Aluminum alloys, which have many advantages such as high specific strength, high specific stiffness, good processing performance, excellent corrosion resistance, electrical and thermal conductivity, and recyclability, have broad application prospects in aerospace, rail transportation, automobiles, ships and other fields. With the continuous improvement of the thrust-to-weight ratio of aircraft engines and the continuous increase in the flight speed of aerospace hypersonic vehicles, stringent requirements of "lightweight, high heat resistance, and high strength" are put forward for aluminum alloy structural parts, and some important parts such as some parts in supersonic engines have complex structures and high requirements for precision. At present, traditional heat-resistant aluminum alloys are mainly cast, and cast heat-resistant aluminum alloys are mostly 2-series and 4-series aluminum alloys, but their room temperature and high temperature performance are not ideal, and complex shapes and structures cannot be formed. Additive manufacturing technology (AM) is considered to be the "engine" of the third industrial revolution, and laser powder bed fusion technology (LPBF) is considered to be one of the most promising additive manufacturing technologies, with high forming accuracy, great design flexibility, and huge advantages in complex structure forming. However, during the LPBF process, extremely high cooling rates will generate great thermal stress, which increases the thermal cracking tendency of aluminum alloys. Series 2, 6, and 7 aluminum alloys will all produce thermal cracks and cannot be printed. Currently, common printable aluminum alloys include Al-Si alloys and Al-Mg-RE alloys, which already have high room temperature strength, but these alloys perform poorly in high temperature environments above 250°C. For heat-resistant aluminum alloys, eutectic Al-Fe, Al-Ni, and Al-Ce alloys are filled with eutectics at the end of solidification, and can also be printed and shaped, while maintaining good performance at high temperatures, but their performance at room temperature is average. Therefore, it is of great significance to develop a new type of heat-resistant aluminum alloy with good formability and good room temperature and high temperature performance. Summary of the invention

[0003] In view of the problems existing in the existing technology for preparing heat-resistant aluminum alloys, the present invention proposes a laser additive manufacturing novel heat-resistant Al-Si-Fe-Ni alloy and a preparation method thereof.

[0004] The present invention provides a new type of heat-resistant Al-Si-Fe-Ni alloy manufactured by laser additive manufacturing, which comprises the following components by mass percentage: Si 10-14%, Fe 1.5-2.5%, Ni 1.45-2.5%, and the balance is Al. The alloy is manufactured by laser additive manufacturing process.

[0005] As a preferred solution, the alloy, by mass percentage, includes the following components Si 11.5~13.5%, Fe 1.6~2.3%, Ni 1.5~2.2%, and the balance is Al. The present invention introduces Fe and Ni elements into commercial additive manufacturing Al-Si alloy, and the room temperature performance and high temperature performance of the alloy are significantly improved. The raw material ratio used in the present invention must be strictly implemented in accordance with the above requirements. If the addition ratio of Si is too small, the processing window of the alloy will be lowered, which is not conducive to industrial production, and the low content of Si will also reduce the room temperature performance of the alloy; if the addition ratio of Si is too large, the alloy will become hard and brittle, and it is easy to generate needle-shaped β-AlSiFe phase, which reduces the mechanical properties of the alloy; if the addition ratio of Fe and Ni is less than 1.45wt%, the strengthening phase AlFeNi cannot be formed; if the addition ratio of any component of Fe and Ni is greater than 2.2wt%, the elongation of the alloy will be significantly reduced.

[0006] As a further preferred embodiment, the alloy comprises the following components, by mass percentage: Si 11.8-12.2%, Fe 1.8-2.2%, Ni 1.5-1.6%, and the balance is Al.

[0007] The invention provides a preparation method of a novel heat-resistant Al-Si-Fe-Ni alloy by laser additive manufacturing. The novel heat-resistant Al-Si-Fe-Ni alloy is prepared on a substrate by using Al-Si-Fe-Ni alloy powder as a raw material through a laser powder bed melting technology. The parameters of the laser powder bed melting technology include: a laser power of 190-230 W, a laser scanning speed of 1100-1300 mm / s, a scanning spacing of 0.1-0.12 mm, a scanning strategy of 60-70° interval between two adjacent layers in the scanning direction, a powder thickness of 0.02-0.04 mm, and a substrate temperature of 70-85°C. The laser powder bed melting technology is implemented under a protective atmosphere.

[0008] The present invention provides a preparation method of a novel heat-resistant Al-Si-Fe-Ni alloy by laser additive manufacturing, wherein the Al-Si-Fe-Ni alloy ingot is subjected to remelting and degassing treatment, and then Al-Si-Fe-Ni alloy powder is prepared by gas atomization; the Al-Si-Fe-Ni alloy powder is spread on a substrate and formed layer by layer by LPBF, and the Al-Si-Fe-Ni alloy powder has a particle size of 5 to 40 μm.

[0009] When applied in industry, computer software is used to design and generate the three-dimensional model required for laser powder bed fusion forming; then the Al-Si-Fe-Ni alloy ingot is remelted and degassed and then prepared by a gas atomization method to obtain Al-Si-Fe-Ni alloy powder, which is then formed layer by layer on an AlSi10Mg substrate by laser powder bed fusion to obtain an aluminum alloy with excellent heat resistance.

[0010] As a preferred solution, the alloy forms a eutectic AlFeNi cellular structure at high temperature, and the AlFeNi phase is not easy to grow at high temperature, and the two synergistically enable the alloy to have excellent high-temperature properties.

[0011] Preferably, the preferred parameters for laser powder bed fusion printing are: under a high-purity nitrogen or high-purity argon protective atmosphere, the laser power is 215~225W, the laser scanning speed is 1100~1150mm / s, the scanning spacing is 0.1~0.12mm, the scanning strategy is that the scanning direction of two adjacent layers is 67° apart, the powder thickness is 0.02~0.04mm, and the substrate temperature is 70~75℃.

[0012] As a preferred solution, when the Al-Si-Fe-Ni alloy is composed of the following mass percentage components: 12% Si, 2% Fe, 1.5% Ni, and the balance is Al, the main parameters of its laser powder bed melting technology process are: under a high-purity nitrogen or high-purity argon protective atmosphere, the laser power is 220W, the laser scanning speed is 1100mm / s, the scanning spacing is 0.1mm, the scanning strategy is that the scanning direction of two adjacent layers is separated by 67°, the powder thickness is 0.03mm, and the substrate temperature is 70°C.

[0013] The printed product obtained by the present invention has a unique layered molten pool structure, in which Al / Si cellular structure exists in the center of the molten pool, wherein Fe and Ni elements are evenly distributed around the cellular structure, thereby improving the stability of the eutectic cellular structure, and the particle size of the cellular structure is 100-300nm. In addition, the AlFeNi phase formed at the boundary of the molten pool is dispersedly distributed, and its particle size is 50-200nm. At 300°C, the eutectic Si network is destroyed, but the Fe and Ni elements are still retained around the cellular structure, and the cellular structure is transformed from the eutectic cellular structure to the elemental cellular structure, because the diffusion coefficients of the Fe and Ni elements are much smaller than the diffusion coefficient of Si, and the AlFeNi phase is not easy to grow at high temperature, and the two cooperate to promote the alloy to maintain good mechanical properties at high temperature.

[0014] Under the optimal printing process parameters, the density of the printed product is 99.6%, the hardness is 174.9HV, the maximum tensile strength is 469MPa, the yield strength is 342MPa, and the elongation is 2.8-3.5% at room temperature, which shows good room temperature mechanical properties.

[0015] Under the optimal printing process parameters, the maximum tensile strength of the printed product at 300°C high temperature stretching is 271MPa, and the elongation is 13.6~14.5%. The tensile strength at 400°C high temperature stretching is 98MPa, and the elongation is 21.5~23.0%, which has excellent high temperature mechanical properties.

[0016] Compared with the prior art, the laser additive manufacturing Al-Si-Fe-Ni heat-resistant alloy and the preparation method thereof of the present invention have the following advantages:

[0017] 1) Through the laser powder bed melting technology, the present invention solves the problem of hollowing out and forming complex shapes of heat-resistant aluminum alloys as a whole, simplifies the processing process, shortens the preparation cycle, does not require a mold, reduces the manufacturing cost, and is suitable for the production of complex heat-resistant aluminum alloy components.

[0018] 2) In the preparation method provided by the present invention, the Al-Si-Fe-Ni alloy powder prepared by gas atomization adopts the LPBF process, and the dense crack-free forming of the Al-Si-Fe-Ni alloy is achieved by optimizing the process parameters and components, and the density reaches 99.6%. At room temperature, the ultimate tensile strength of the alloy is greater than or equal to 445MPa, the yield strength is greater than or equal to 325MPa, and the elongation is greater than or equal to 1.5%. The mechanical properties are much higher than those of cast and forged aluminum alloys. After optimization, the mechanical properties of the product can be further improved.

[0019] 3) In the preparation method provided by the present invention, the prepared Al-Si-Fe-Ni alloy will form a eutectic AlFeNi cellular structure at high temperature, and the AlFeNi phase is not easy to grow at high temperature. The two work together to enable the alloy to have excellent high-temperature performance. Under the optimal process parameters, the maximum tensile strength at 300°C is 271MPa, and the elongation is 13.6~14.5%. The tensile strength at 400°C is 98MPa, and the elongation is 21.5~23.0%. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0021] Figure 1 This is a microscopic morphology of the Al-Si-Fe-Ni alloy powder described in Example 1;

[0022] Figure 2 The metallographic image of the Al-Si-Fe-Ni alloy in the scanning direction described in Example 1;

[0023] Figure 3 A scanning electron microscope image of the Al-Si-Fe-Ni alloy construction direction described in Example 1;

[0024] Figure 4 The scanning electron microscope images of the cellular structure of the Al-Si-Fe-Ni alloy described in Example 1 after heat treatment at different temperatures for 1 hour (a 200°C, b 250°C, c 300°C, d 350°C);

[0025] Figure 5The scanning electron microscope images of the AlFeNi phase of the Al-Si-Fe-Ni alloy described in Example 1 after heat treatment at different temperatures for 1 h (a 200°C, b 250°C, c 300°C, d 350°C);

[0026] from Figure 1 It can be seen that the powder is spherical as a whole, with a small amount of planetary powder on the surface. The powder particle size is 5~40μm, with good fluidity, and is suitable for laser powder bed melting forming.

[0027] from Figure 2 It can be seen that the prepared Al-Si-Fe-Ni alloy samples are dense and crack-free, with fewer surface defects, proving that the designed alloy has good applicability for LPBF.

[0028] from Figure 3 It can be seen that the designed alloy has a unique layered molten pool structure. There is a eutectic Al / Si cellular structure in the center of the molten pool, in which Fe and Ni elements are evenly distributed around the cellular structure, which improves the stability of the eutectic cellular structure. Due to the remelting effect, AlFeNi phase is formed at the boundary of the molten pool.

[0029] from Figure 4 and Figure 5 It can be seen that at 300°C, the eutectic Si network is destroyed, but the Fe and Ni elements are still retained around the cellular structure, and the cellular structure is transformed from the eutectic cellular structure to the elemental cellular structure; at the same time, when the temperature gradually increases, the size of the AlFeNi phase changes little, and there is no obvious growth, which can significantly hinder the movement of dislocations. The two work together to enable the alloy to maintain good mechanical properties at high temperatures. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is described clearly and completely below. Obviously, the specific implementation of the present invention cannot be limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.

[0031] Example 1

[0032] The alloy ingot is remelted and degassed and then gas atomized to prepare an Al-Si-Fe-Ni alloy, wherein the mass percentage composition of the Al-Si-Fe-Ni alloy powder is: 12% Si, 2.0% Fe, 1.5% Ni, and the balance is Al, and the particle size range of the Al-Si-Fe-Ni alloy powder is 13-37 μm. The alloy powder is placed in a vacuum drying oven and dried for 12 hours at a drying temperature of 80°C. The three-dimensional model required for LPBF is designed and generated using computer software, and the vacuum-dried alloy powder is evenly spread on an AlSi10Mg substrate, and is printed layer by layer according to the constructed three-dimensional model to obtain parts with complex shapes; wherein the printing parameters are: laser power 220W, laser scanning speed 1100mm / s; scanning spacing 0.1mm, scanning strategy is 67° interval between adjacent layers in the scanning direction, powder thickness 0.03mm, substrate temperature 70°C, and protective gas is pure argon.

[0033] The aluminum alloy sample (printed state) prepared in this embodiment was characterized. The relative density of the Al-Si-Fe-Ni alloy formed by the printing parameters was 99.5%, the maximum tensile strength at room temperature was 469 MPa, the yield strength was 342 MPa, and the elongation was 2.8~3.5%. The maximum tensile strength at 300°C was 271 MPa, and the elongation was 13.6~14.5%. The tensile strength at 400°C was 98 MPa, and the elongation was 21.5~23.0% (the average elongation was 22.3%).

[0034] Example 2

[0035] The alloy ingot is remelted and degassed and then gas atomized to prepare an Al-Si-Fe-Ni alloy, wherein the mass percentage composition of the Al-Si-Fe-Ni alloy powder is: 12.5% ​​Si, 2.0% Fe, 1.6% Ni, and the balance is Al, and the particle size range of the Al-Si-Fe-Ni alloy powder is 13-37 μm. The alloy powder is placed in a vacuum drying oven and dried for 12 hours at a drying temperature of 80°C. The three-dimensional model required for LPBF is designed and generated using computer software, and the vacuum-dried alloy powder is evenly spread on an AlSi10Mg substrate, and is printed layer by layer according to the constructed three-dimensional model to obtain parts with complex shapes; wherein the printing parameters are: laser power 200W, laser scanning speed 1100mm / s; scanning spacing 0.1mm, scanning strategy is 67° interval between adjacent layers in the scanning direction, powder thickness 0.03mm, substrate temperature 70°C, and protective gas is pure argon.

[0036] The aluminum alloy sample (printed state) prepared in this embodiment was characterized. The relative density of the Al-Si-Fe-Ni alloy formed by the printing parameters was 99.6%, the maximum tensile strength at room temperature was 459 MPa, the yield strength was 381 MPa, the elongation was 1.5-2.0%, the maximum tensile strength at 300°C was 263 MPa, the elongation was 12.5-13.6%, the tensile strength at 400°C was 93 MPa, and the elongation was 19.8-21.0%.

[0037] Example 3

[0038] The alloy ingot is remelted and degassed and then gas atomized to prepare Al-Si-Fe-Ni alloy, wherein the mass percentage composition of the Al-Si-Fe-Ni alloy powder is: 12% Si, 2.3% Fe, 2.2% Ni, and the balance is Al, and the particle size range of the Al-Si-Fe-Ni alloy powder is 13-37 μm. The alloy powder is placed in a vacuum drying oven and dried for 12 hours at a drying temperature of 80°C. The three-dimensional model required for LPBF is designed and generated using computer software, and the vacuum-dried alloy powder is evenly spread on an AlSi10Mg substrate, and is printed layer by layer according to the constructed three-dimensional model to obtain parts with complex shapes; wherein the printing parameters are: laser power 230W, laser scanning speed 1300mm / s; scanning spacing 0.12mm, scanning strategy is 67° interval between adjacent layers in the scanning direction, powder thickness 0.03mm, substrate temperature 70°C, and protective gas is pure argon.

[0039] The aluminum alloy sample (printed state) prepared in this embodiment was characterized. The relative density of the Al-Si-Fe-Ni alloy formed by the printing parameters was 99.2%, the maximum tensile strength at room temperature was 449 MPa, the yield strength was 330 MPa, and the elongation was 3.0-3.5%. The maximum tensile strength at 300°C was 251 MPa, and the elongation was 12.5-13.3%. The tensile strength at 400°C was 83 MPa, and the elongation was 18.2-19.7%.

[0040] Comparative Example 1

[0041] The alloy ingot is remelted and degassed and then gas atomized to prepare Al-Si-Fe-Ni alloy, wherein the mass percentage composition of the Al-Si-Fe-Ni alloy powder is: 12.5% ​​Si, 1.9% Fe, 1.6% Ni, and the balance is Al, and the particle size range of the Al-Si-Fe-Ni alloy powder is 13-37 μm. The alloy powder is placed in a vacuum drying oven and dried for 12 hours at a drying temperature of 80°C. The three-dimensional model required for LPBF is designed and generated using computer software, and the vacuum-dried alloy powder is evenly spread on an AlSi10Mg substrate, and is printed layer by layer according to the constructed three-dimensional model to obtain parts with complex shapes; wherein the printing parameters are: laser power 260W, laser scanning speed 1500mm / s; scanning spacing 0.1mm, scanning strategy is 67° interval between adjacent layers in the scanning direction, powder thickness 0.03mm, substrate temperature 70°C, and protective gas is pure argon.

[0042] The aluminum alloy sample (printed state) prepared in this embodiment was characterized. The relative density of the Al-Si-Fe-Ni alloy formed by the printing parameters was 96.3%, the maximum tensile strength at room temperature was 382 MPa, the yield strength was 295 MPa, and the elongation was 2.6~3.4%. The maximum tensile strength at 300°C was 196 MPa, and the elongation was 9.0~10.1%. The tensile strength at 400°C was 65 MPa, and the elongation was 14.0~14.9%.

[0043] Comparative Example 2

[0044] The alloy ingot is remelted and degassed and then gas atomized to prepare an Al-Si-Fe-Ni alloy, wherein the mass percentage composition of the Al-Si-Fe-Ni alloy powder is: 12% Si, 3.0% Fe, 2.5% Ni, and the balance is Al, and the particle size range of the Al-Si-Fe-Ni alloy powder is 13-37 μm. The alloy powder is placed in a vacuum drying oven and dried for 12 hours at a drying temperature of 80°C. The three-dimensional model required for LPBF is designed and generated using computer software, and the vacuum-dried alloy powder is evenly spread on an AlSi10Mg substrate, and is printed layer by layer according to the constructed three-dimensional model to obtain parts with complex shapes; wherein the printing parameters are: laser power 200W, laser scanning speed 1100mm / s; scanning spacing 0.1mm, scanning strategy is 67° interval between adjacent layers in the scanning direction, powder thickness 0.03mm, substrate temperature 70°C, and protective gas is pure argon.

[0045] The aluminum alloy sample (printed state) prepared in this embodiment was characterized. The relative density of the Al-Si-Fe-Ni alloy formed by the printing parameters was 98.9%, the maximum tensile strength at room temperature was 365 MPa, the yield strength was 299 MPa, the elongation was 1.1-1.4%, the maximum tensile strength at 300°C was 209 MPa, the elongation was 13.6-14.5%, the tensile strength at 400°C was 60 MPa, and the elongation was 17.0-18.2%.

[0046] Comparative Example 3

[0047] The alloy ingot is remelted and degassed and then gas atomized to prepare an Al-Si-Fe-Ni alloy, wherein the mass percentage composition of the Al-Si-Fe-Ni alloy powder is: 12.5% ​​Si, 1.3% Fe, 1.0% Ni, and the balance is Al, and the particle size range of the Al-Si-Fe-Ni alloy powder is 13-37 μm. The alloy powder is placed in a vacuum drying oven and dried for 12 hours at a drying temperature of 80°C. The three-dimensional model required for LPBF is designed and generated using computer software, and the vacuum-dried alloy powder is evenly spread on an AlSi10Mg substrate, and is printed layer by layer according to the constructed three-dimensional model to obtain parts with complex shapes; wherein the printing parameters are: laser power 220W, laser scanning speed 1300mm / s; scanning spacing 0.1mm, scanning strategy is 67° interval between adjacent layers in the scanning direction, powder thickness 0.03mm, substrate temperature 70°C, and protective gas is pure argon.

[0048] The aluminum alloy sample (printed state) prepared in this embodiment was characterized. The relative density of the Al-Si-Fe-Ni alloy formed by the printing parameters was 98.8%, the maximum tensile strength at room temperature was 399 MPa, the yield strength was 315 MPa, and the elongation was 2.8-3.6%. The maximum tensile strength at 300°C was 169 MPa, and the elongation was 11.1-12.0%. The tensile strength at 400°C was 49 MPa, and the elongation was 13.0-14.3%.

[0049]

[0050] Table 1 shows the room temperature and high temperature performance comparison of each embodiment and comparative example as well as the Al-12Si alloy formed by LPBF. Among them, the density of the alloys prepared in Examples 1 to 3 is above 99%. Figure 2In the metallographic diagram, there are no cracks on the sample surface and very few pores, indicating that the Al-Si-Fe-Ni alloy is highly applicable to the LPBF process. However, due to the excessively high laser power and the excessively fast scanning speed in Comparative Example 1, a large number of pores and defects exist in the prepared alloy, resulting in a significant decrease in its performance relative to the embodiment. Furthermore, the Fe and Ni contents in Comparative Example 2 are too high, and the Fe and Ni contents in Comparative Example 3 are too low, both resulting in a certain degree of decrease in its room temperature strength and high temperature strength relative to the embodiment. Therefore, the ratio of elements in the alloy and the change of LPBF process parameters must be carried out within the scope provided by the present invention. Only in the technical solution provided by the present invention can an AlFeNi phase that is not easy to grow at high temperatures be formed, and a eutectic AlFeNi cellular structure be formed at high temperatures, and the two can synergistically improve the high temperature mechanical properties of the alloy.

[0051] The four comparison examples in the above table are from "Die-cast multicomponent near-eutectic and hypoeutectic Al-Si-Ni-Fe-Mn alloys: Microstructures and mechanical properties" (Materials Science & Engineering A 872 (2023) 144977).

[0052] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. It should be pointed out that a person skilled in the art can make several improvements and modifications within the scope of the technical principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A laser additive manufacturing method for a novel heat-resistant Al-Si-Fe-Ni alloy, characterized in that: Calculated by mass percentage, the composition includes: 10-14wt% Si, 1.5-2.5wt% Fe, 1.45-2.5wt% Ni, and the balance is Al.

2. A laser additive manufacturing novel heat-resistant Al-Si-Fe-Ni alloy according to claim 1, characterized in that: Calculated by mass percentage, it includes the following components: 11.5-13.5% Si, 1.8-2.3% Fe, 1.5-2.2% Ni, and the balance is Al.

3. The laser additive manufacturing novel heat-resistant Al-Si-Fe-Ni alloy according to claim 1, characterized in that: The alloy includes the following components by mass percentage: Si 11.8-12.2%, Fe 1.8-2.2%, Ni 1.5-1.6%, and the balance is Al.

4. The method for preparing the novel heat-resistant Al-Si-Fe-Ni alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: A novel heat-resistant Al-Si-Fe-Ni alloy was prepared on a substrate by laser powder bed melting technology using Al-Si-Fe-Ni alloy powder as raw material; parameters of the laser powder bed melting technology included: laser power of 190-230 W, laser scanning speed of 1100-1300 mm / s, scanning spacing of 0.1-0.12 mm, scanning strategy of 60-70° interval between two adjacent layers in scanning direction, powder thickness of 0.02-0.04 mm, and substrate temperature of 70-85°C; the laser powder bed melting technology was implemented under a protective atmosphere.

5. The method for preparing a novel heat-resistant Al-Si-Fe-Ni alloy according to claim 3, characterized in that: The parameters of laser powder bed fusion printing are: under high-purity nitrogen or high-purity argon protective atmosphere, laser power is 215~225W, laser scanning speed is 1100~1150mm / s, scanning spacing is 0.1~0.12mm, scanning strategy is 67° interval between two adjacent layers in scanning direction, powder thickness is 0.02~0.04mm, and substrate temperature is 70~75℃.

6. The method for preparing a novel heat-resistant Al-Si-Fe-Ni alloy according to claim 5, characterized in that: When the Al-Si-Fe-Ni alloy is composed of the following mass percentage components: 12% Si, 2% Fe, 1.5% Ni, and the balance is Al, the parameters of its laser powder bed melting technology process are: under a high-purity nitrogen or high-purity argon protective atmosphere, the laser power is 220W, the laser scanning speed is 1100mm / s, the scanning spacing is 0.1mm, the scanning strategy is that the scanning direction of two adjacent layers is separated by 67°, the powder thickness is 0.03mm, and the substrate temperature is 70°C.

7. A novel heat-resistant Al-Si-Fe-Ni alloy manufactured by laser additive manufacturing according to claim 5 or 6, characterized in that: It has a unique layered molten pool structure, with Al / Si cellular structure in the center of the molten pool, wherein Fe and Ni elements are evenly distributed around the cellular structure, and the particle size of the cellular structure is 100~300nm. In addition, the AlFeNi phase formed at the boundary of the molten pool is dispersedly distributed, and its particle size is 50~200nm; at 300℃, the eutectic Si network is destroyed, but the Fe and Ni elements are still retained around the cellular structure, and the cellular structure is transformed from the eutectic cellular structure to the elemental cellular structure.

8. The laser additive manufacturing novel heat-resistant Al-Si-Fe-Ni alloy according to claim 6, characterized in that: The density of the printed product is 99.6%, the hardness is 174.9HV, the maximum tensile strength is 469MPa, the yield strength is 342MPa, and the elongation is 2.8-3.5%.

9. The laser additive manufacturing Al-Si-Fe-Ni heat-resistant alloy according to claim 6, characterized in that: The maximum tensile strength of the printed product is 271MPa at 300°C, and the elongation is 13.6~14.5%. The tensile strength is 98MPa at 400°C, and the elongation is 21.5~23.0%.